2013
DOI: 10.1007/s00404-013-2932-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of different size-hysteroscope in office hysteroscopy: our experience

Abstract: Our result suggests that the hysteroscope size plays a pivotal role in the acceptance and for the success of office hysteroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…According to the literature, the rate of non-completion of the office hysteroscopy process is 1.3–5.2%. 26 Thus the rate of failure in our study was acceptable. The “no-touch” technique is considered suitable, based on the number of successful office hysteroscopies in our practice.…”
Section: Discussionmentioning
confidence: 51%
“…According to the literature, the rate of non-completion of the office hysteroscopy process is 1.3–5.2%. 26 Thus the rate of failure in our study was acceptable. The “no-touch” technique is considered suitable, based on the number of successful office hysteroscopies in our practice.…”
Section: Discussionmentioning
confidence: 51%
“…It's obvious that IV sedation might have precluded subjective pain assessment by the patients. In addition, the chosen warm temperature of 40°C is far from the physiological body temperature [11,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have mentioned greater intensity of pain at extremes of age and in cases that had undergone prior surgical cervical interventions. It is likely that colic triggered by uterine contractility could be provoked by cooler temperatures, which is considered hostile to the uterus [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…At our institution, we adopted a specific EST based on detailed criteria, according to the clinical presentation. In fact, we classified ESTs as follows: (I) dilatation and curettage (D&C), performed in case of active uterine bleeding that usually prevents the view of the cavity; (II) outpatient biopsy with 5 mm Bettocchi’s hysteroscope, using either micro scissors and/or forceps ( 22 ), performed in case of anesthesiological contraindication; (III) diagnostic hysteroscopy with 5 mm Bettocchi’s hysteroscope followed by D&C, performed in case no suspicious endometrial area was found for selective biopsy; (IV) operative hysteroscopy with cervical dilatation, using saline solution for uterine distention and resectoscope, performed in all the remaining cases and, finally; (V) operative hysteroscopy with cervical dilatation, performed as previously mentioned and followed by D&C, in case of subjective impression of scanty material obtained after resectoscopic biopsy. All procedures, except outpatient hysteroscopy, were performed under general anesthesia.…”
Section: Methodsmentioning
confidence: 99%